Teacher training and pedagogical courses in the Nalchik district in the second half of the 19th and early 20th centuries - Laura, Urusmambetova (Kavkazologiya, 2025)
The article is devoted to the study of the teacher training system and the functioning of pedagogical courses in the Kabarda (Nalchik) district in the second half of the XIX – early XX century. The paper analyzes the legal framework governing the organization of teacher education during this period, and examines the specifics of the implementation of educational policy in a multi-ethnic region. The government's measures aimed at overcoming the shortage of teachers are shown. Initially, teachers' seminaries focused on the training of rural teachers became the main form of staff training. However, their limited effectiveness contributed to the spread of short-term pedagogical courses in the Russian Empire as a more operational tool for teacher training. The article analyzes the socio-historical and cultural factors that determined the effectiveness of educational initiatives. Examples of both successful and ineffective courses organized within the same school district are given. A comparison of their results allows us to draw conclusions about the conditions affecting the effectiveness of pedagogical courses. The article examines the evolution of various forms of pedagogical training in the Kabardian (Nalchik) district, from the first courses of K. Atazhukin and special departments in the 1870s to two–year courses under the guidance of I.M. Karmova, as well as short-term professional development courses. This paper traces the relationship of these initiatives with the educational policy of the Caucasian Educational District and the regional specifics of the Kabardian (Nalchik) district. The use of archival sources revealed both the continuity of these forms and their limited effectiveness due to administrative decisions, co-financing from local societies, and a weak methodological base. The results of the study expand the understanding of the inclusion of the Caucasus in the educational space of the Russian Empire and the importance of early initiatives to develop education and primary school education in the region. The article is valuable for historians and researchers of the history of education who study the processes of formation of teaching staff and the functioning of pedagogical institutes in multinational regions of the Russian Empire.